THE INFLUENCE OF WORK DISCIPLINE AND EDUCATIONAL COMPETENCY ON EMPLOYEE PERFORMANCE IN PERSONNEL AGENCYAND HUMAN RESOURCES DEVELOPMENT NORTH LAMPUNG DISTRICT - Febriyantina, Reni; Junaidi, Junaidi (University of Sang Bumi Ruwa Jurai, 2023)
Human resources have an important role for the organization because human resources as system managers, so that this system continues to run, of course in managing it must pay attention to important aspects such as competence, discipline, education and training as well as the level of comfort at work so that the employees concerned can be encouraged to provide all capabilities according to the needs of the organization. Human resources with good performance will eventually produce good employee performance as well. Employee performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. This research was conducted at the Staffing and Human Resources Development Agency in Lampung Utara Regency. The type of research used in this research is field research, which is quantitative in nature where the explanation is objective by explaining the existing approaches, with a total sample of 19 respondents. The results of this study are that the variable Work Discipline (X1) influences employee performance (Y) by 61.1%, Educational Competency Variable (X2) influences employee performance (Y) by 53.9%, and Work Discipline (X1) and Competence Education ( X2) simultaneously influences employee performance (Y) by 54.9%